2021
DOI: 10.3390/pathogens10040464
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and In Vitro Activity of N-Substituted 1,2-Benzisothiazol-3(2H)-ones against Dengue Virus NS2BNS3 Protease

Abstract: Several new N-substituted 1,2-benzisothiazol-3(2H)-ones (BITs) were synthesised through a facile synthetic route for testing their anti-dengue protease inhibition. Contrary to the conventional multistep synthesis, we achieved structurally diverse BITs with excellent yields using a two-step, one-pot reaction strategy. All the synthesised compounds were prescreened for drug-like properties using the online Swiss Absorption, Distribution, Metabolism and Elimination (SwissADME) model, indicating their favourable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Batool et al (2021) investigated a few N -substituted 1,2-benzoisothiazol-3(2H)-ones 117 – 123 ( Table 22 ) via a one-pot and two-step protocol [ 183 ]. Upon screening the synthesized compounds, it was observed that the compounds inhibited the DENV2 NS2B/NS3 protease significantly.…”
Section: Mixed Heterocyclic Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Batool et al (2021) investigated a few N -substituted 1,2-benzoisothiazol-3(2H)-ones 117 – 123 ( Table 22 ) via a one-pot and two-step protocol [ 183 ]. Upon screening the synthesized compounds, it was observed that the compounds inhibited the DENV2 NS2B/NS3 protease significantly.…”
Section: Mixed Heterocyclic Scaffoldsmentioning
confidence: 99%
“… Ortho-substitution displays greater inhibition as compared to the para-substitution. [ 183 ] Inhibits DENV2. Various substituents present on the phenyl ring of the truncated benzothiazole scaffolds affect greater inhibition.…”
Section: Summarizing the Sar Analysis Of Reported Heterocyclic Scaffo...mentioning
confidence: 99%
“…Hybrid pharmacophores generated by a combination of two individual pharmacophores with 1,2-Benzisothiazol-3(2H)-one (BIT) as the skeleton have been proven to show synergistic effects in inhibition of the DENV-2 NS2B-NS3 [ 85 ]. It was observed that BITs bind to the protease in vicinity of the catalytic triad.…”
Section: Ns2b-ns3 Protease Inhibitorsmentioning
confidence: 99%
“…The BITs containing aromatic substitutions at the N-atom-like compounds 31 with 2-methyl-4-nitrophenyl, 32 with 2-chlorophenyl, and 33 2,6-dichlorophenyl showed the highest protease inhibition with an IC 50 of 2.56 ± 1.03 µM, 2.01 ± 0.98 µM, and 5.28 ± 1.89 µM, respectively. The DENV-2 infection assay showed that two BITs, the compound 32 reduced viral infectivity by 1.4 orders of magnitude and the compound 33 reduced the viral infectivity by about six fold [ 85 ].…”
Section: Ns2b-ns3 Protease Inhibitorsmentioning
confidence: 99%
“…[7][8][9] Thus, taking into account the pivotal role played in the viral replication, the DENV NS2B/NS3 protease has been extensively exploited as a drug target for the discovery and development of direct-acting antivirals against dengue. [10,11] Even though several peptidic or peptidomimetic compounds containing reactive "warheads," [12][13][14][15][16][17][18] and noncovalent small organic molecules [19][20][21][22][23][24][25][26] have been identified as inhibitors of DENV NS2B/NS3 protease, no inhibitor has reached clinical development as a specific antidengue drug. This may be due to unfavorable drug metabolism and pharmacokinetic (DMPK) properties and/or lower target affinity of known inhibitors.…”
Section: Introductionmentioning
confidence: 99%